Penyelesaian SP2DK Dan Dampaknya Terhadap Penyajian Laporan Keuangan Pada PT Z Di Gowa - Fransiska, Ninda Bella; Sarjono, Bayu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: “The Letter of Request for Explanation of Data and/or Information,” often referred to as an SP2DK in Indonesia, is an instrument used by the Directorate General of Taxes (DGT) to test the level of taxpayer compliance in their tax reporting, based on data deemed inappropriate or containing indications of irregularities. This study aims to determine how Z L td carried out the SP2DK resolution process in Gowa Regency, and its impact on the presentation of the company’s financial statements.Methods: The research method used is a descriptive, qualitative case study. Data collection techniques included direct observation, in-depth interviews with management and financial staff, and analysis of relevant tax documents and financial statements.Results: The focus of the study was on the SP2DK clarification stages, from identifying the data requested by the tax authority, preparing responses and supporting evidence, to administrative completion and recording its impact in the company’s accounting system. The results show that completing the SP2DK encouraged Z Ltd to correct prior tax reporting, which affected adjustments to accounting records, the recognition of tax expenses, and the presentation of tax obligations in the financial statements. This process also encourages companies to improve the accuracy and transparency of financial reporting and strengthen internal control systems related to tax compliance. It can be concluded that completing the SP2DK not only has implications for taxation aspects but also contributes to improving the quality of financial reporting and overall corporate governance. Keywords: SP2DK, financial statements, taxation, tax compliance, accounting